The development of corporate governance in China / Z. Jun Lin, Ming Liu, Xu Zhang - Lin, Z. Jun; Ming, Liu (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2006)
This paper delineates the development of corporate governance in China in the course of the recent market-oriented economic reforms. The four-stage evolutionary progresses of corporate governance practices in the country are outlined, while the main deficiencies in the existing governance practices of the Chinese companies are analyzed. In addition, the most recent efforts made by the Chinese government in order to promote capital market reforms and improve corporate governance practices are described. It is argued that a series of corporate governance practices originating in western countries have been gradually adopted or experimented in China although the actual effects of their implementation in practice remains to be seen.